Descripción de los estados inmaduros de Delphacodes haywardi y notas acerca de su comportamiento en condiciones de laboratorio (Homoptera: Delphacidae) - Marino de Remes Lenicov, Ana María (1996)
Delphacodes haywardi Muir is one of the most widely distributed delphacids in crops within the wet Pampean region in Argentina; however, up to day, its biology is poorIy known. The anatomy of all preimaginal stages, life span, and reproductive behavior were studied under controlled conditions in individual glass cages containing pieces of leaves of Sorghumhalepense. In order to study the reproductive behavior, plants of Cynodon dactylon grown at four leaves stage have been used. Coloration pattern is diagnostic for the species in all nymphal instars; all them have a black spot on the front flanked by light areas in each side. Under the conditions cited aboye, this plant-hopper oviposited groups of 2 to 8 eggs in the shaft, Each female laid 10.33 eggs per day; at 22.50 C the duration of the egg stage averaged 11.5 days and the whole nymphal stage 22.5 days. The viability was 82.1%and the survivency 58.62%.